Association between breakfast-eating habit and attention-concentration in primary school children: a cross-sectional study in Badung District - Ni Made Ari Sukmandari; Ni Wayan Septarini; Gede Ngurah Indraguna Pinatih (Universitas Udayana, 2018)
Background and purpose: One of the main benefits of breakfast eating habit for schoolchildren is to maintain the attention concentration. The current trend shows a steady decline in the breakfast-eating habit among primary school children. This present study aims to examine the association between breakfast-eating habit and attention-concentration in primary school children. Methods: A cross-sectional study was conducted involving 160 primary school students year 5 and 6. Samples were selected from six public primary schools within two villages. There were a total of 16 classes of year 5 and 6 in these six schools, and five classes were selected randomly. All students from the selected classes included in the study. Attention concentration was measured using a digit symbol test, and breakfasteating habit and total calories intake were measured using the recall 24 hours and a standardised questionnaire. Multivariate analysis with logistic regression was employed to examine the association between breakfast-eating habit and attention-concentration. Results: The majority of students were found to have good concentration (60.63%), with breakfast-eating habit (75.00%), and consumed sufficient amount of calories (53.13%). Our multivariate analysis found a significant association between breakfast-eating habit and attention-concentration among schoolchildren (AOR=14.0; 95%CI: 4,9–67,8). Conclusions: Students with breakfast-eating habit tend to have a good attention-concentration. The total calories intake during breakfast is not associated with attention-concentration among primary school students in Badung District.